Forecast of economic consequences of the first stage of the Russian-Ukrainian war for Russia : (loss of personnel and weapons and military equipment, costs, possible consequences) - Semenenko, Oleh; Dobrovolskyi, Yuzef; Koverga, Victoriia; Mytchenko, Serhii; Motrunych, Ivan; Yarmolchyk, Maria (Social Development and Security, 2022)
Purpose: on the basis of statistics on losses and expenses of Russia in the Russian-Ukrainian war to predict the possible consequences for the Russian economy for different durations of the active phase of hostilities in Ukraine, taking into account the effects of economic sanctions against Russia imposed on the world for attacking Ukraine. Design/Method/Approach: the main research methods are methods of statistical analysis, military-economic analysis, expert survey and forecasting methods. Findings: statistical information was collected and an analysis of Russia’s losses and expenses during the 38 days of the Russian-Ukrainian war was conducted; On the basis of the obtained results, the possible consequences for the Russian economy for different periods of the war were predicted, and the views on the further development of events for Russia and Ukraine were determined.. Theoretical implications: the main result of research on the subject of the article is an assessment of the state of Russia’s economy over the duration of the war. Paper type: descriptive and calculation-analytical.